The role of ar-rahn in enhancing financial inclusion : a structural equation modeling approach - Azila Abdul Razak; Fidlizan Muhammad; Mohd Yahya Mohd Hussin; Zuraidah Zainol; Fatimah Salwa Abd. Hadi (Penerbit Universiti Kebangsaan Malaysia, 2017)
This study examines the relationship between financial inclusion and the adoption of ar-rahn financing in enhancing the well-being of its customers throughout Malaysia. Data distributed via questionnaire to 239 respondents were analyzed using descriptive and structural equation modeling. The results indicate that there is a positive relationship between financial inclusion and ar-rahn’s financing adoption. In addition, the adoption of ar-rahn among customers improves the well-being of individuals and society. This paper contributes to the existing literatures and provide new insights on how financial inclusion could increase the adoption of ar-rahn financing and consequently the individual and societal well-being.